Long-term persistence of symptoms of dyspnoea in COVID-19 patients. (February 2022) - Nguyen, Nhu Ngoc; Hoang, Van Thuan; Dao, Thi Loi; Meddeb, Line; Lagier, Jean-Christophe; Million, Matthieu; Raoult, Didier; Gautret, Philippe
Highlights: Out of 838 contacted patients, 496 (59.2%) answered the questionnaire. 123/496 (24.8%) patients reported persistent dyspnoea. Age ≥ 45 years old is associated with persistent dyspnoea.